Quarterly GDP Revisions in G-20 Countries : Evidence from the 2008 Financial Crisis - Shrestha, Manik; Marini, Marco (Washington, D.C. : International Monetary Fund, 2013)
This paper presents a statistical analysis of revisions in quarterly gross domestic product (GDP) of the Group of Twenty countries (G-20) since 2000. The main objective is to assess whether the reliability of early estimates of quarterly GDP has been weakened from the turmoil of the 2008 financial crisis. The results indicate that larger and more downward revisions were observed during the years 2008 and 2009 than in previous years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: GDP Estimate; GDP Revision; Gross Domestic Product; Quarterly National Accounts; WP; United Kingdom